Based on a Decision Tree Model for Exploring the Risk Factors of Smartphone Addiction Among Children and Adolescents in China During the COVID-19 Pandemic - Duan, Li; He, Juan; Li, Min; Dai, Jiali; Zhou, Yurong; Lai, Feiya; Zhu, Gang (Frontiers in Psychiatry, 2021)
Background: Smartphone addiction has emerged as a major concern among children and adolescents over the past few decades and may be heightened by the outbreak of COVID-19, posing a threat to their physical and mental health. Then we aimed to develop a decision tree model as a screening tool for unrecognized smartphone addiction by conducting large sample investigation in mainland China. Methods: The data from cross-sectional investigation of smartphone addiction among children and adolescents in mainland China (n=3,615) was used to build models of smartphone addiction by employing logistic regression, visualized nomogram and decision tree analysis. Results: Smartphone addiction was found in 849 (23.5%) of the 3615 respondents. According to the results of logistic regression, nomogram, and decision tree analyses, Internet addiction, hours spend on smartphone during the epidemic, levels of clinical anxiety symptoms, fear of physical injury, and sex were used in predictive model of smartphone addiction among children and adolescents. The C-index of the final adjusted model of logistic regression was 0.804. The classification accuracy, sensitivity, specificity, positive predictive value, negative predictive value, and AUC area of decision tree for detecting smartphone addiction were 87.3%,71.4%, 92.1%, 73.5%, 91.4%, and 0.884, respectively. Conclusions: It was found that the incidence of smartphone addiction among children and adolescents is significant during the epidemic. The decision tree model can be used to screen smartphone addiction among them. Findings of the five risk factors will help researchers and parents assess the risk of smartphone addiction quickly and easily.